Bilateral ovarian fibromas with duplex collecting system and ectopic ureter in an 11-year-old girl: a case report with genetic analysis - Zhang, Lei; Dong, Chunhua; Yang, Cuihua; Gui, Meng (Frontiers in Pediatrics, 2026)
BackgroundBilateral ovarian fibromas in children are exceedingly rare. Their coexistence with congenital anomalies of the kidney and urinary tract (CAKUT) has not been reported.Case presentationAn 11-year-old girl presented with abdominal pain and lifelong urinary dribbling. Imaging revealed bilateral ovarian masses and a left duplex collecting system with a dilated upper-pole ureter inserting ectopically into the posterior urethra. Serum tumor markers including CA125 were within normal limits. No ascites or peritoneal deposits were identified. Laparoscopic bilateral tumor excision preserved normal ovarian tissue; histopathology confirmed ovarian fibromas with low proliferative index. Three months later, laparoscopic excision of the ectopic distal ureteral segment and ipsilateral ureteroureterostomy completely resolved urinary symptoms. Trio whole-exome sequencing identified heterozygous variants in SUFU (p.Asp182Asn) and FN1 (p.Asn649Ile), both inherited from unaffected parents. At 12-month follow-up, the patient had spontaneous menarche with preserved ovarian function.ConclusionsThis unprecedented dual genitourinary presentation expands the clinical spectrum of pediatric ovarian fibromas. Combined SUFU and FN1 variants suggest possible shared mesodermal developmental susceptibility. Fertility-preserving surgery combined with staged urologic reconstruction achieved full functional recovery.